Blood derived treatment from two allogeneic sources for severe dry eye associated to keratopathy: a multicentre randomised cross over clinical trial - Campos, Emilio; Versura, Piera; Buzzi, Marina; Fontana, Luigi; Giannaccare, Giuseppe; Pellegrini, Marco; Lanconelli, Nico; Brancaleoni, Alessandra; Moscardelli, Fabiana; Sebastiani, Stefano; Vaselli, Cristiana; Randi, Vanda (British journal of ophthalmology, 2020)
AimTo compare the efficacy of cord blood and peripheral adult donor blood serum eyedrops, controlled for growth factor content, in the treatment of severe dry eye diseases (DED) resistant to conventional therapy.MethodsThis was a multicentre randomised, double-masked, cross-over clinical trial. Sixty patients diagnosed as severe DED, associated to persistent corneal epithelial defects were randomised and equally assigned to group A (treated with cord blood serum (CBS)) or group B (treated with PBS), eyedrops administered eight times/day for 1 month. Primary outcome was the pretreatment and post-treatment change in corneal fluorescein staining. Secondary outcomes included the pretreatment and post-treatment change in Ocular Surface Disease Index (OSDI) questionnaire and Visual Analogue Score (VAS) of subjective symptoms, Schirmer I test, tear break-up time and conjunctival staining. Patients with relapse in signs or symptoms after further 2 months switched to the remaining group for one additional month. Data were statistically analysed (p<0.05).ResultsCorneal staining was more significantly reduced after the CBS treatment, both VAS and OSDI score reduction was observed in both groups, but group A reported significantly less grittiness and pain. Nineteen patients shifted in the crossover period, the within individual comparison confirmed a better recovery in the CBS treatment period. Reduction in epithelial damage was positively associated with epidermal growth factor, transforming growth factorα and platelet-derived growth factor content. Levels of interleukins (IL-13) were positively associated with symptom decrease.ConclusionsOverall, DED signs improved after both CBS and PBS treatments, with potential advantages of CBS for subjective symptoms and corneal damage reduction.Clinical trial registration NCT03064984.